2017
DOI: 10.3233/jem-160434
|View full text |Cite
|
Sign up to set email alerts
|

A note on how to realize the full potential of the EU-SILC data

Abstract: Die Dis cus si on Pape rs die nen einer mög lichst schnel len Ver brei tung von neue ren For schungs arbei ten des ZEW. Die Bei trä ge lie gen in allei ni ger Ver ant wor tung der Auto ren und stel len nicht not wen di ger wei se die Mei nung des ZEW dar.Dis cus si on Papers are inten ded to make results of ZEW research prompt ly avai la ble to other eco no mists in order to encou ra ge dis cus si on and sug gesti ons for revi si ons. The aut hors are sole ly respon si ble for the con tents which do not neces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The description of the EU-SILC database, along with the country and variables coverage and a complete documentation can be found at: http://ec.europa.eu/eurostat/web/microdata/european-union-statistics-on-income-and-living-conditions. The routines to transform original csv files into the Stata format come from Gesis (prepared by Heike Wirth, http://www.gesis.org/en/missy/materials/EU-SILC/setups).10 The description of the EU-SILC potential for the purpose of research applications can be found inBerger and Schaffner (2016). Iacpovou (2012) discuss issues concerning the use of EU-SILC for cross-national analysis.…”
mentioning
confidence: 99%
“…The description of the EU-SILC database, along with the country and variables coverage and a complete documentation can be found at: http://ec.europa.eu/eurostat/web/microdata/european-union-statistics-on-income-and-living-conditions. The routines to transform original csv files into the Stata format come from Gesis (prepared by Heike Wirth, http://www.gesis.org/en/missy/materials/EU-SILC/setups).10 The description of the EU-SILC potential for the purpose of research applications can be found inBerger and Schaffner (2016). Iacpovou (2012) discuss issues concerning the use of EU-SILC for cross-national analysis.…”
mentioning
confidence: 99%
“…Different features of EU‐SILC are described in Iacovou et al . () and in Berger and Schaffner (). The primary purpose of this survey, which is the successor to ECHP, is to provide information on the distribution of income and social exclusion in Europe.…”
Section: Estimationmentioning
confidence: 93%
“…A typical longitudinal release covers 4 years, but will not contain data from all rotational groups. Instead, one rotational group is followed up for 4 years, a second for 3 years, and a third for 2 years (see Berger and Schaffner, for an illustration of this structure). Appending observations from different releases therefore allows an increase in the total sample size: starting from the 2011 release, which covers the years 2008–11, we use the 2010 release to add observations from a new rotational group for the years 2007–10 for each available country.…”
Section: Estimationmentioning
confidence: 99%
“…As EU SILC research has its limitations (Berger & Schaffner, 2017;Lacovou et al, 2012), the study additionally uses data from the Ministry of Finance. These data come from annual information on the PIT settlement and annual information on flat-rate tax on recorded revenues.…”
Section: Methodsmentioning
confidence: 99%